Pendampingan Etika Komunikasi Dalam Meningkatkan Kredibilitas Di Tingkat Pemerintahan - NUR HOLIFAH (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
It is necessary to increase the capacity of kelurahan government officials in terms of their knowledge and abilities when carrying out their duties and responsibilities to balance the dynamics and development of the community in the kelurahan. Without these efforts, it is impossible for development to succeed given the limited resources available at the kelurahan level. According to Masdar (2005) there are four main missions in developing the apparatus, namely: first, realizing a professional state administration system. Second, develop bureaucratic ethics and a transparent work culture. Third, accountable, sensitive and responsive to the aspirations of the community. Fourth, realizing a public service management system that is fast, precise and satisfying. Given the complexity of the aspects or fields to be developed at the lowest level of government, one of the aspects that first needs to be developed is to increase the capacity of the village government apparatus in carrying out government administration tasks, in addition to strengthening community and institutional participation as well as other aspects of other. The development of communication ethics in increasing the credibility of the village apparatus will indirectly have a very good impact on government agencies. So in general it can be said that the development of human resource capacity through ethical communication skills. will have many positive effects on all sub-district apparatus and levels of society because it will accommodate all the conveniences of service that will be enjoyed by the community. This means that communication ethics is not only devoted to one group but to all kelurahan apparatuses. Seeing the condition of public services in Tambak Wedi Village, Kenjeran District, Surabaya City, at least there are some problems experienced by Tambak Wedi Village. First, the lack of understanding of the urgency of good communication ethics in providing a public service. Second, the lack of leadership commitment in realizing the principles of good communication ethics for village government employees in providing public services. Third, there are no effective and efficient public service standards. Fourth, human resources. Fifth, there is no will, commitment to implementation and internal coordination. Sixth, facilities and infrastructure. The solution offered in this community service program is the strengthening of village apparatus human resources in collaboration with the Immigration Office Class I TPI Tanjung Perak. First, the activity was carried out by sharing discussions related to strengthening or improving the human resources of urban village apparatus through communication ethics in providing public services, secondly, FGD activities aimed at solving problems in Tambak Wedi Village, Kenjeran District, Surabaya City. Third, the preparation of public service standards in accordance with Law No. 25 of 2009 and Permenpan No. 36 of 2012.